Mixed Convection in Fluid Superposed Porous Layers - Dixon, John M.; Kulacki, Francis A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This Brief describes and analyzes flow and heat transport over a liquid-saturated porous bed. The porous bed is saturated by a liquid layer and heating takes place from a section of the bottom. The effect on flow patterns of heating from the bottom is shown by calculation, and when the heating is sufficiently strong, the flow is affected through the porous and upper liquid layers. Measurements of the heat transfer rate from the heated section confirm calculations. General heat transfer laws are developed for varying porous bed depths for applications to process industry needs, environmental sciences, and materials processing. Addressing a topic of considerable interest to the research community, the brief features an up-to-date literature review of mixed convection energy transport in fluid superposed porous layers.
Introduction -- Mathematical Formulation and Numerical Methods -- Numerical Results -- Measurement of Heat Transfer Coefficients -- Summary of Findings -- References -- Appendices.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Materials; Materials -- Analysis; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Thermodynamics; Materials Engineering; Characterization and Analytical Technique